Analysis of Liquidity Ratios and Profitability Ratios as Financial Performance Indicators of PT Kalbe Farma Tbk for the 2021-2024 Period - Risma Aulia Salsabila; Desy Suryani; Martinus Wahyu Purnomo (LPPPIPublishing, 2026)
The pharmaceutical industry has experienced dynamic shifts in financial conditions at the COVID-19 pandemic. Consequently, it is important to re-examine the financial status of PT Kalbe Farma Tbk in the post-pandemic era, given prior studies have focused only on periods preceding 2024. This study aims to analyze the status and trends of liquidity ratios and profitability ratios for PT Kalbe Farma Tbk from 2021 to 2024. A non-statistical descriptive quantitative method was employed using horizontal analysis comparing financial ratio values ​​across years to identify developmental patterns. The data utilized consisted of PT Kalbe Farma Tbk’s annual consolidated financial statements for the 2021–2024 period, obtained from the company’s official website and the Indonesia Stock Exchange. Calculation results indicate that the company's liquidity ratios consistently remained well above safety benchmarks, with Current Ratios ranging from 377% to 491%, Quick Ratios from 2019% to 301%, and Cash Ratios from 89% to 176%; meanwhile, profitability ratios weakened in 2023 (NPM fell to 9%, ROA to 10%, and ROE to 12%) before recovering in 2024. High liquidity levels demonstrate the company's ample capacity to meet short-term obligations, whereas the 2023 decline in profitability was primarily driven by rising operating expenses that outpaced sales growth. The concluded that PT Kalbe Farma Tbk retains a strong capacity to settle short-term obligations, though it needs to enhance operational efficiency to optimize profitability. These findings are intended to serve as a reference for management and investors when assessing the company's financial health prior to making decisions.